Late Jurassic of the Russian platform: Ammonite evolution and paleoenvironments - Mitta, V. V.; Bogomolov, Yu. I. (Bulletin of the Geological Society of Greece, 2007)
During the terminal age of Late Jurassic a considerable decrease in ammonoid taxonomic diversity and distinct changes of ammonite shell morphotypes are recorded in the Central Russian Basin. By the end-Volgian, ammonites are represented by only two genera belonging to a single family, which differ markedly in their shell form. The end-Jurassic decrease in ammonoid biodiversity started in the mid-Volgian and is correlated first of all with shallowing of the sea